Phase transformations of the Ge8Sb2-xBixTe11 chalcogenide system and their potential application as a phase-change material - Karabyn, Vasyl (Univerzita Pardubice, 2020)
The thesis deals with the preparation, characterization and, in particular, with the switching properties of phase-change material (PCM) thin films. The films were deposited using Flash Thermal Evaporation (FE) and the Pulsed Laser Deposition (PLD) technique. Thesis is divided into three main chapters. The first chapter starts with Introduction, where the background information and the main motivation for the PCM research is presented, followed by an overview about the principle of phase-change materials operation. Then in more detail properties of crystalline and amorphous phase in GST are presented. At the end of this chapter is discussed the application of PCM.
Fázové transformace v chalkogenidovém systému Ge8Sb2-xBixTe11 a jeho aplikační potenciál jako materiálu pro záznam informací
Keywords: materiály s fázovou změnou (PCM); tenké filmy; Ge8Sb2-xBixTen; tepelné žíhání; fs laserové pulsní záření; krystalizace; phase-change materials (PCM); thin films; Ge8Sb2-xBixTen; thermal annealing; fs laser pulse irradiation; crystallization